A phoswich alpha/beta detector for monitoring in the site of Fukushima Daiichi Nuclear Power Station. (January 2023) - Morishita, Yuki; Takasaki, Koji; Kitayama, Yoshiharu; Tagawa, Akihiro; Shibata, Takuya; Hoshi, Katsuya; Kaneko, Junichi H.; Higuchi, Mikio; Oura, Masatoshi
Abstract: Alpha contamination and high concentrations of beta contamination can be found inside the reactor buildings at the Fukushima Daiichi Nuclear Power Station (FDNPS). This study proposes a newly developed phoswich alpha/beta detector that can discriminate alpha and beta particles emitted from the alpha and beta contaminations in the FDNPS site. The phoswich alpha/beta detector is made up of two layers of scintillators that detect alpha and beta particles. The first layer is an octagonal, 50 mm diameter, 40-μm-thick plastic scintillator that measures alpha particles, while the second layer is an octagonal, 50 mm diameter, 50-μm-thick Gd₂Si₂O₇ (GPS) scintillator that measures beta particles. The combination of the two scintillators improves the ability to distinguish between alpha and beta particles. The two layers of scintillators were optically coupled to an 8 × 8 multianode photomultiplier tube (MA-PMT) with 50 mm × 50 mm through a 3-mm-thick light guide (glass plate). An eight-channel 14-bit 500 MS/s digitizer was fed with four output signals. Python programming was used to analyze the collected voltage waveforms. The pulse shape discrimination (PSD) method was used to detect alpha particles in high beta particle and high gamma-ray (comparable to gamma-ray dose rate near the FDNPS reactor building) environments. Due to a 23.3% full width at half maximum (FWHM) energy resolution for alpha particles, the detector can be used to distinguish between nuclear fuel materials such as plutonium and its radon progeny (Po-214). Moreover, the detector could distinguish alpha particles from 137 Cs gamma rays with a dose rate background up to 9.0 mSv/h. It is the first to demonstrate that the developed phoswich detector can be used to discriminate and measure alpha and beta particles of the actual contaminated FDNPS samples. As a result, this detector will be effective as an air monitoring device for alpha and beta radionuclide contamination measurement in real time. Highlights: We developed a new alpha/beta phoswich detector for the Fukushima Daiichi Nuclear Power Station (FDNPS) site. The first layer is a 40-µm-thick plastic scintillator, while the second layer is a 50-μm-thick Gd₂Si₂O₇ (GPS) scintillator. The PSD method was used to detect alpha particles from high beta particle and high gamma-ray environments. The developed phoswich detector can be used to discriminate and measure alpha and beta particles of the actual contaminated FDNPS samples.